Transdermal delivery of artemisinins for treatment of pre-clinical cerebral malaria. (August 2021) - Zech, Johanna; Dzikowski, Ron; Simantov, Karina; Golenser, Jacob; Mäder, Karsten
Abstract: Transdermal drug delivery avoids complications related to oral or parenteral delivery - the need for sterility, contamination, gastrointestinal side effects, patient unconsciousness or nausea and compliance. For malaria treatment, we demonstrate successful novel transdermal delivery of artemisone (ART) and artesunate. The incorporation of ART into a microemulsion (ME) overcomes the limitations of the lipophilic drug and provides high transcutaneous bioavailability. ART delivery to the blood (above 500 ng/ml) was proved by examining the sera from treated mice, using a bioassay in cultured Plasmodium falciparum. Skin spraying of ART-ME eliminated P. berghei ANKA in an infected mouse model of cerebral malaria (CM) and prevented CM, even after a late treatment with a relatively small amount of ART (13.3 mg/kg). For comparison, the artesunate (the most used commercial artemisinin) formulation was prepared as ART. However, ART-ME was about three times more efficient than artesunate-ME. The solubility and stability of ART in the ME, taken together with the successful transdermal delivery leading to animal recovery, suggest this formulation as a potential candidate for transdermal treatment of malaria. Graphical abstract: Image 1